New media and visual communication in social networks - Kir, Serpil, 1985- (Advances in multimedia and interactive technologies (AMIT) book series., 2020)
"This book examines communication strategies in the context of social media and new digital media platforms and explores the effects of visual communication on social networks, visual identity, television, magazines, newspapers, and more"--